2022
DOI: 10.1093/geronb/gbac003
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Disparities in Advance Care Planning: Assessing the Role of Subjective Life Expectancy

Abstract: Objectives Persistent race disparities in advance care planning (ACP) are troubling, given Black and Hispanic older adults’ elevated risk of disease, some dementias, and receipt of care that may not align with their preferences. A potentially important yet underexplored explanation for these disparities is subjective life expectancy (SLE), or beliefs about one’s future survival which may impel or impede ACP. Methods Data are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Recent work has suggested an effect of subjective life expectancy on informal ACP use and identified more optimistic life expectancy estimates among Black older adults and more pessimistic estimates among Hispanic older adults compared to White older adults. However, racial/ethnic differences in ACP persisted after controlling for subjective life expectancy, suggesting that other factors may play a larger role (Lou & Carr, 2022), Another alternative explanation involves unmeasured patient-provider factors. Clinicians are less likely to initiate ACP conversations with individuals with whom there are perceived or real barriers to communication (e.g., language barriers, differences in communication style, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has suggested an effect of subjective life expectancy on informal ACP use and identified more optimistic life expectancy estimates among Black older adults and more pessimistic estimates among Hispanic older adults compared to White older adults. However, racial/ethnic differences in ACP persisted after controlling for subjective life expectancy, suggesting that other factors may play a larger role (Lou & Carr, 2022), Another alternative explanation involves unmeasured patient-provider factors. Clinicians are less likely to initiate ACP conversations with individuals with whom there are perceived or real barriers to communication (e.g., language barriers, differences in communication style, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Our target is that all Veterans in the participating CNH and HBPC programs are given an opportunity to discuss their goals and document their LST preferences. Several studies have documented that nonwhite patients, including Veterans, are less likely to engage in goals of care discussions and have lower rates of LST and SAPO completion [51][52][53]. Eliminating racial and ethnic disparities in the LST template and SAPO completion is important; thus, to evaluate the Reach of the PERSIVED interventions, we will compare the proportions of nonwhite/Hispanic Veterans with LST templates (HBPC) or SAPOs (CNH) vis-à-vis the white, non-Hispanic Veterans.…”
Section: Reachmentioning
confidence: 99%
“…The National Coalition for Hospice and Palliative Care 1 has identified culturally appropriate end-of-life (EOL) care planning as a US national priority. Racial and ethnic disparities in EOL care planning are well documented 2-4 . Rao et al 5 found that only 18% of diverse patients had an advance directive (AD), as compared with 34% of Whites.…”
mentioning
confidence: 99%
“…Racial and ethnic disparities in EOL care planning are well documented. [2][3][4] Rao et al 5 found that only 18% of diverse patients had an advance directive (AD), as compared with 34% of Whites.…”
mentioning
confidence: 99%